Purification of Natural Antibodies Against Tau Protein by Affinity Chromatography - Krestova, Michala; Hromadkova, Lenka; Ricny, Jan (Methods in molecular biology (Clifton, N.J.), 2017)
Natural antibodies are now widely studied for their therapeutical potential. Therefore, their isolation and subsequent characterization is desired. Here, we describe an isolation method for natural anti-tau antibodies from human plasma by utilization of affinity chromatography with epoxy-activated copolymer resin. The evalution of isolation efficiency and avidity of isolated antibodies is decribed by modified indirect ELISA assay.
Keywords: intravenózní imunoglobuliny; Immunosorbent Techniques; autoprotilátky; tau Proteins; Intravenous immunoglobulin; Immunopurification; Natural antibodies; lidé; Immunoglobulins, Intravenous; Antibodies; chromatografie afinitní; imunosorpční techniky; Immobilization; Human plasma; Autoantibodies; Tau protein; Chromatography, Affinity; Immunoreactivity; proteiny tau; protilátky; Humans